A chevron-notched bowtie micro-beam bend test for fracture toughness measurement of brittle materials. (15th April 2017) - Cui, Fiona Yuwei; Vinci, Richard P.
Abstract: A micro-mechanical fracture testing method has been developed that uses a bowtie-shaped micro-beam specimen with a chevron notch. This clamped-clamped specimen can produce stable crack growth in brittle materials. Cyclic loading causes progressive crack extension, thereby producing multiple fracture toughness results in one experiment. The symmetric geometry eliminates the mixed mode fracture that exists in single-ended cantilevers. A 3D finite element analysis model was used to relate the crack length to the beam compliance, and then to the fracture toughness. The results of tests using fused quartz and glass-ceramic materials match very well with published fracture toughness values. Graphical abstract: